Factors of FTTH deployment in Japan: A panel data analysis - Yuji Akematsu; Sobee Shinohara; Masatsugu Tsuji (International Telecommunications Society (ITS), 2012)
In accordance with the development of broadband services, interests are focused on the deployment of optical fiber and various reports and researches are published, including Next Generation Connectivity by the Berkman Center, Harvard University, and Indicators of Broadband Coverage by OECD. These analyze the international comparison of broadband penetration or how U.S. and EU lag behind. Less analysis was, however, spent how Japan constructed the most successful FTTH networks all over the country. The objective of this paper is to identify factors promoting deployment of Japanese FTTH in the competitive environments utilizing the panel data analysis and the prefectural panel data of subscribers. Major deregulations including unbundling, openness of facilities, connection charges and collocations were already implemented. The problem occurred in this process, however, is that the share of NTT locals in the FTTH market locals has been increasing and reached more than 70%. Moreover, the NTT locals' share in the total four broadband markets including FTTH, cable modem, ADSL and FWA becomes also more than 50%. This paper attempts to explain this reason. Recently, however, the situation has been changing, namely competition has been more severe in the metropolitan and populated areas, which is promoted by power companies and KDDI. This paper also focuses on current changes in the FTTH market, and explains how these are different from the previous period. Lessons learned from Japanese experiences will provide good reference to other economies to deploy FTTH.
Keywords: 330; FTTH; broadband connectivity; panel data analysis; unbundling; migration; HHI